Optimalisasi Potensi BUMDes Sendang Karya Desa Purworejo Kabupaten Kudus melalui Peningkatan Kapasitas Anggota dalam Budidaya Jamur Tiram - Nindya Arini; Farida Yuliani; Endang Dewi Murrinie (Universitas Pahlawan Tuanku Tambusai, 2026)
Village-Owned Enterprises (BUMDes) play a strategic role in developing local potential-based productive businesses to support food security. However, limited knowledge and technical skills in oyster mushroom cultivation hinder the development of this business unit. This community service program aimed to enhance the capacity of members of BUMDes Sendang Karya, Purworejo Village, Kudus Regency, through training and mentoring in oyster mushroom cultivation. The program employed focus group discussions, educational outreach, hands-on practice, mentoring, and monitoring. The results demonstrated improved knowledge and technical skills in mushroom house construction, cultivation techniques, crop maintenance, and environmentally friendly pest management using light traps. Continuous mentoring enabled participants to overcome cultivation constraints and apply improved cultivation practices. This program strengthened the capacity of BUMDes to develop sustainable productive enterprises, thereby supporting local food security and improving the rural community's economic resilience.